THE RIGHT CRITERIA IN SELECTING THE SUPPLIER OF LOTTO FABRIC RAW MATERIAL IN CONVECTION INDUSTRY BY USING AHP AND TOPSIS METHODS - Endang Widuri Asih; Rizka Marchamah; Cyrilla Indri Parwati; Andrean Emaputra (Center for Study and Journal Management FTI UMI, 2020)
Family Sport Clothing convection is Mr. Raharjo’s family business in textile industry which produces training pants, made of lotto fabric. The company only has one criterion in supplier selection process, and in this convection is the cost. In this convection, problems that usually occur in selecting the supplier of raw materials are the production process is delayed since the raw materials are not enough; the quality of the raw materials does not meet the company standards; and supplier that does not deliver on time. This study was conducted with the aim of identifying the criteria used in selecting supplier and determining the ranking or the best supplier priority. The researcher implemented AHP (Analytical Hierarchy Process) method by distributing questionnaires to the owners of convection, and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) by measuring the shortest distance between positive ideal solutions and the longest distance with negative ideal solutions. The criteria were adopted from previous researches, and processed by using Pareto diagrams. Based on the results of calculations using Pareto diagram, the criteria used in this study are quality, cost, service, delivery, feasibility, and capacity. Based on the results of calculation using AHP method, the order of the most prioritized criteria is: quality (0.37), cost (0.29), capacity (0.13), feasibility (0.12), delivery process, (0.07,) and service (0.03). In addition, the priority order of the suppliers based on TOPSIS is: Libeng Kiantana (0.45), Yudi Hartono (0.23), Abdul Ghofur (0.23), Panorama Shop (0.06) and Indigenous Face Shop (0.02).